2012
DOI: 10.1128/jcm.01194-12
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Bacteremia Caused by the Acinetobacter calcoaceticus-Acinetobacter baumannii Complex

Abstract: This study investigated the clinical and microbiological characteristics of patients with recurrent bacteremia caused by the Acinetobacter calcoaceticus-Acinetobacter baumannii (ACB) complex at a medical center. All ACB complex isolates associated with recurrent bacteremia were identified to the genomic species level using a 16S-23S rRNA gene intergenic spacer sequence-based method. Genotypes were determined by the random amplified polymorphic DNA patterns generated by arbitrarily primed PCR and by pulsotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In this study, we observed a substantial rate (16.7%) of recurrent bacteraemia due to ESBL-producing bacteria. This finding is similar to that reported for non-typhoid Salmonella bacteraemia (15.7%) [8] but differs from those observed in bacteraemia due to Staphylococcus aureus (20.3%) [9], E. coli (6.3%) [10], Acinetobacter baumannii (5.6%) [11] and Streptococcus pneumoniae (2.3%) [12]. Through PFGE analysis, we further found that 67.8% of the cases were caused by identical strains.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we observed a substantial rate (16.7%) of recurrent bacteraemia due to ESBL-producing bacteria. This finding is similar to that reported for non-typhoid Salmonella bacteraemia (15.7%) [8] but differs from those observed in bacteraemia due to Staphylococcus aureus (20.3%) [9], E. coli (6.3%) [10], Acinetobacter baumannii (5.6%) [11] and Streptococcus pneumoniae (2.3%) [12]. Through PFGE analysis, we further found that 67.8% of the cases were caused by identical strains.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study has reported a substantial rate (12%) of recurrent bacteraemia, and several independent predictors have been identified, including healthcare-associated origins, polymicrobial Gram-positive or fungal aetiology, inappropriate empirical antimicrobial therapy, related infection foci within the abdomen or endocardium and the use of intravenous catheters [7]. Other studies have demonstrated that recurrent bacteraemia occurs at a rate of 2.3% to 20.3% for a variety of specific pathogens [8][9][10][11][12]. However, the incidence and risk factors associated with recurrent bacteraemia by ESBL-EC or ESBL-KP have not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…2 As Acinetobacter calcoaceticus, Acinetobacter baumannii, Acinetobacter genomic species 3, and Acinetobacter genomic species 13TU are very closely related, it has been proposed to refer to these species as the A. calcoaceticus-A. baumannii complex (ACB complex).…”
Section: Reply To Su and Chaomentioning
confidence: 99%
“…Since the clinically relevant members of the ACB complex cannot be separated by currently available commercial identification systems, such as the Vitek 2, Phoenix, and Microscan systems, A. baumannii isolates in our study represent the ACB complex. 2 Species identification with commercial identification systems that are currently used in clinical microbiology laboratories remains problematic, and molecular methods have been developed and validated for identification of Acinetobacter species. 3 Given that A. baumannii, Acinetobacter genomic species 3, and Acinetobacter genomic species 13TU share important clinical and epidemiological characteristics, the need for species identification of the ACB complex in clinical microbiology laboratories is questionable.…”
Section: Reply To Su and Chaomentioning
confidence: 99%
See 1 more Smart Citation